Do Insulin Replacement and Omega3 Protect the Male Reproductive Function of the Streptozotocin-Induced Diabetic Mice? - Atefe Yaghoubi; Abbas Shahedi; Hakime Akbari; Seyed Noureddin Nematollahi-Mahani (Journal of Nutrition and Metabolism)
Diabetes mellitus (DM), the most common metabolic disease, might affect different organs such as male reproductive system. Experiments have shown that n-3 fatty acids could improve male reproductive function. Present study was performed to examine the effects of omega3 on sperms and testicular parameters in diabetic mice. Adult NMRI male mice were randomly divided into intact and diabetic groups (n=8). Streptozotocin-induced diabetic animals were divided into 4 groups of diabetic-saline (Dia-Sa), diabetic-insulin (Dia-Ins), diabetic-omega3 (Dia-omg3), and diabetic-insulin-omega3 (Dia-Ins-omg3). Following confirmation of diabetes, different treatments including 3 U/100 g insulin subcutaneously and 400 mg/kg omega3 orally were administered, where applicable according to the treatment groups. Thirty-five days later, the sperm number, motility, progression, and normal morphology were determined. Also, testes diameters and structure including germinal epithelium thickness, seminiferous tubule diameters, Leydig cell number, and testosterone level were assessed. Sperm number, viability, fast motility, testes volume, and serum testosterone level decreased insignificantly in the Dia-Sa group compared with the intact animals. Neither insulin replacement nor omega3 administration could significantly improve the outcome. We might conclude that short periods of diabetes could not significantly affect the male reproductive function. In addition, insulin replacement and/or omega-3 supplementation does not have any profound effects on male reproductive system.